ANALISA PENENTUAN OPEN END PADA PELAKSANAAN SQUEEZE CEMENTING DI ZONA POROUS SUMUR A LAPANGAN B - Rexnord Samuel Simanungkalit (President University, 2018)
Cementing is the process of pushing a number of slurry which flows from the bottom of the casing shoes to rise to the annulus between the casing and formation. The cement slurry will harden so that it binds between the casing and the borehole wall. According to the purpose of cementing can be divided into two, namely Initial Cementing (Primary Cementing) and Second Cementing or Cementing Repair (Secondary or Remedial Cementing). If the Primary Cementing results are not perfect and have problems, then Secondary or Remedial Cementing will be done. Secondary or Remedial Cementing can be divided into three parts, namely Squeeze cementing, Re-cementing and Plug-back cementing. In this case, the author emphasizes on one of the Secondary or Remedial Cementing namely Squeeze Cementing.